PENGARUH MOTIVASI KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI BADAN KEPEGAWAIAN DAERAH KABUPATEN NIAS UTARA - Peringatan Harefa; Eliagus Telaumbanua (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to determine: a. to find out whether there is a partial effect of Work Motivation on the Performance of the Regional Personnel Agency of North Nias Regency. b. to find out whether there is a partial effect of Work Ability on the Performance of the Regional Personnel Agency of North Nias Regency. c. to find out how much influence Work Motivation and Work Ability simultaneously on the Performance of the Regional Personnel Agency of North Nias Regency.In this study the formulation of the problem